Pengaruh Religiusitas Dan Keadilan Pajak Pada Sikap Kepatuhan Wajib Pajak (Survei pada Wajib Pajak Orang Pribadi Pada Kantor Wilayah Direktorat Jenderal Pajak Jawa Barat I) - Anggraeni Dwijayanti; Memed Sueb; Arie Pratama (Jurnal Akuntansi dan Pajak, 2021)
The low tax revenue ratio reflects the low level of taxpayer compliance, because the increasing level of compliance will encourage the tax revenue ratio and vice versa. A number of non-economic factors that influence tax compliance behavior are related to religious value (religiosity) and tax justice. This research is a quantitative research developed with a descriptive verification method with a time horizon that is cross section /one shot. The unit of analysis in this study is an individual taxpayer registered at the Regional Office of the Directorate General of Taxes, West Java 1 in 2019. The data analysis technique used in this study uses multiple linear regression. The results showed that taxpayer religiosity and tax justice had a positive and significant effect on taxpayers partially. he magnitude influence of religiosity and tax justice on taxpayers is 73.2%, and 26.8% is contribute from the other variables.